2020
DOI: 10.1186/s12968-020-00667-3
|View full text |Cite
|
Sign up to set email alerts
|

Incremental prognostic value of coronary flow reserve determined by phase-contrast cine cardiovascular magnetic resonance of the coronary sinus in patients with diabetes mellitus

Abstract: Background Although non-invasive assessment of coronary flow reserve (CFR) by cardiovascular magnetic resonance (CMR) provides prognostic information for patients with diabetes mellitus (DM), the incremental prognostic value of CMR-derived CFR remains unclear. Purpose To evaluate the incremental prognostic value of CMR-derived CFR for patients with DM who underwent stress CMR imaging. Materials and methods A total of 309 patients with type 2 DM [69 ± 9 years; 244 (78%) male] assessed between 2009 and 2019 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…It needs to be considered that CSF-based MPR is not only reduced by the presence of obstructive epicardial stenosis—but is also affected by relevant microvascular changes. This notion is further supported by the fact that an incremental prognostic value of CMR-derived MPR was detected for patients with diabetes undergoing stress CMR imaging 21 . The annualized MACE rate was substantially higher in those patients with MPR < 2.0—regardless of the presence or absence of LGE.…”
Section: Discussionmentioning
confidence: 73%
“…It needs to be considered that CSF-based MPR is not only reduced by the presence of obstructive epicardial stenosis—but is also affected by relevant microvascular changes. This notion is further supported by the fact that an incremental prognostic value of CMR-derived MPR was detected for patients with diabetes undergoing stress CMR imaging 21 . The annualized MACE rate was substantially higher in those patients with MPR < 2.0—regardless of the presence or absence of LGE.…”
Section: Discussionmentioning
confidence: 73%
“…Validation studies of this imaging technique have been performed using phantom models [ 33 ], animal experimental models using flow probes [ 18 ] and PET [ 16 ]. Recent studies have shown the prognostic importance of CMR-derived CFR for atherosclerotic diseases, such as CAD [ 20 , 21 ] or diabetes mellitus [ 22 , 23 ]. Additionally, this method is potentially useful for evaluating reduced CFR in patients with non-atherosclerotic diseases, including hypertrophic cardiomyopathy [ 15 , 34 ], dilated cardiomyopathy [ 19 ] and HFpEF [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Phase contrast (PC) cine cardiovascular magnetic resonance (CMR) of the coronary sinus has emerged as a non-invasive means to quantify CFR [ 15 19 ]. Recent studies have shown the prognostic implication of CMR-derived CFR for coronary artery disease [ 20 , 21 ] or diabetes mellitus [ 22 , 23 ]. Regarding HFpEF, the CMR-derived CFR has been found to be significantly lower compared with that in hypertensive left ventricular (LV) hypertrophy and controls, and was correlated with serum brain natriuretic peptide (BNP) level [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most adverse impact was associated with cold and wet weather with low atmospheric pressure, which is common in Helsinki in early winter and late autumn. 39 Despite the numerous literature data on the close dependence of the development and outcomes of MI on heliogeophysical factors, there are studies in which the relationship between the incidence rate and the course of the 11-year solar cycle was not noted, and no connection was found when comparing the monthly incidence with the average monthly values of Wolf numbers, due to which, it seems that the course of CVD is a test incomparably more complex than chemical, leukocyte and epidemiological tests, and its correlation with SA is much more complicated than with simple tests. Similar results were obtained by American researchers for 4 years of studying mortality from coronary insufficiency and CSs (275 million indicators).…”
Section: Resultsmentioning
confidence: 99%